THE DETERMINANT FACTORS OF REGIONAL EXPENDITURE - Septriani Septriani; Handoko Hadiyanto; Retno Agustina Ekaputri (Universitas Tidar, 2023)
The objective of this research is to analyze the determinat factors of regional expenditure budget of district/city in bengkulu province . The data used in this research is secondary data obtained from the Directorate General of Fiscal Balance (Ministry of Finance) and the Central Statistics Agency for 2016-2021 and other supporting reports. The data collected are local own-source revenue (OSR), general allocation funds (GAF), special allocation funds (SAF) and economic growth. The types of data and analysis tools used are panel data and multiple linear regression. Based on the panel data regression results, the best model obtained in this research is the Fixed Effect Model. The results of the study show that partially the General Allocation Fund (GAF) and the Special Allocation Fund (SAF) have a positive and significant impact on district/city regional expenditure budget in Bengkulu Province, and economic growth has a negative and significant effect on district/city regional expenditure budget in Bengkulu Province, while Local Own-Source Revenue (OSR) has no effect on district/city regional expenditure budget in Bengkulu Province. Meanwhile, simultaneously General Allocation Fund (GAF), Special Allocation Fund (SAF), economic growth and local own-source revenue (OSR) have a positive and significant effect on district/city regional expenditure budget in Bengkulu Province with an Adjusted R-squared amount of 89,04 percent, while 10.96 percent is explained by other variables outside the variables of this study.